Analysis of Optical Wireless Communication Links in Turbulent Underwater Channels With Wide Range of Water Parameters - Ata, Yalcin; Kiasaleh, Kamran (IEEE transactions on vehicular technology, 2023)
In this study, the performance of underwater optical wireless communication links is investigated by taking into account turbulence, absorption and scattering effects. Weak turbulent channel is modeled using log-normal distribution while moderate and strong turbulence channels are modeled using gamma-gamma distribution. Rytov variance of Gaussian beam is derived analytically for oceanic turbulence optical power spectrum. Subsequently, scintillation index is calculated using the computed Rytov variance. Moreover, the closed-form expression of bit-error-rate (BER) for underwater wireless optical communication (UWOC) systems using intensity-modulated/direct detection (IM/DD) implementation and on-off-keying (OOK) modulation scheme is obtained. Results show that the performance of wireless optical communication link between two platforms in underwater medium is degraded significantly due to turbulence, absorption and scattering. In fact, as the turbulence level increases, its effect becomes quantitatively comparable to those of absorption and scattering effects. The variation of both scintillation index and BER performance are presented for various underwater medium and communication system parameters, such as chlorophyll concentration, average temperature, average salinity concentration, temperature and dissipation rates, wavelength, link length and receiver aperture size. Optical network and internet of underwater things (IoUT) applications, which are growing day by day and requiring high data rates, will benefit from the results of this study.